Role of Secondary Plant Metabolites on Enteric Methane Mitigation in Ruminants - Ku-Vera, Juan Carlos; Jiménez-Ocampo, Rafael; Valencia-Salazar, Sara Stephanie; Montoya-Flores, María Denisse; Molina-Botero, Isabel Cristina; Arango, Jacobo; Gómez-Bravo, Carlos Alfredo; Aguilar-Pérez, Carlos Fernando; Solorio-Sánchez, Francisco Javier (Frontiers in Veterinary Science, 2020)
The rumen microbiome plays a fundamental role in all ruminant species, it is involved in health, nutrient utilization, detoxification and methane emissions. Methane is a greenhouse gas which is eructated in large volumes by ruminants grazing extensive grasslands in the tropical regions of the world. Enteric methane is the largest contributor to the emissions of greenhouse gases originating from animal agriculture. A large variety of plants containing secondary metabolites essential oils (terpenoids), tannins, saponins and flavonoids have been evaluated as cattle feedstuffs and changes in volatile fatty acid proportions and methane synthesis in the rumen have been assessed. Alterations to the rumen microbiome may lead to changes in diversity, composition and structure of the methanogen community. Legumes containing condensed tannins such as Leucaena leucocephala have shown a good methane mitigating effect when fed at levels of up to 30-35% of ration dry matter in cattle as a result of the effect of condensed tannins on rumen bacteria and methanogens. It has been shown that saponins disrupt the membrane of rumen protozoa, thus decreasing the numbers of both protozoa and methanogenic archaea. Trials carried out with cattle housed in respiration chambers have demonstrated the enteric methane mitigation effect in cattle and sheep of tropical legumes such as Enterolobium cyclocarpum and Samanea saman which contain saponins. Essential oils are volatile constituents of terpenoid or non-terpenoid origin which impair energy metabolism of archaea and have shown reductions of up to 26 % in enteric methane emissions in ruminants. There is emerging evidence showing the potential of flavonoids as methane mitigating compounds, but more work is required in vivo to confirm preliminary findings. From the information hereby presented, it is clear that plant secondary metabolites can be a rational approach to modulate the rumen microbiome and modify its function, some species of rumen microbes improve protein and fiber degradation and reduce feed energy loss as methane in ruminants fed tropical plant species.